Analisis Senyawa Metabolit Sekunder dan Uji Toksisitas Fraksi N-Heksan dan Fraksi Etil Asetat Ekstrak Etanol Daun Ketepeng Cina (Cassia alata L.) - Nunung Pratiwi; Dahlan; Wa Ode Mulyana (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
This study aims to determine the group of secondary metabolite contained in n-hexane fraction and ethyl acetate fraction ethanol extracts chinese ketepeng leaves and determine the level of toxicity n-hexane fraction and ethyl acetate fraction extracts chinese ketepeng leaves on Artemia salina L. Extraction using maceration technique, the secondary metabolite compounds was determined by phytochemical method, and toxicity testing on Artemia salina L. larvae by BSLT method. Larval mortality data were analyzed by probit analysis to determine the LC50 value in each n-hexane fraction and ethyl acetate fraction. The results of phytochemical screening showed the presence the n-hexan fraction contains flavonoids and steroid compounds, while the ethyl acetate fraction contains steroid and tannin compounds. The results of toxicity testing showed that each fraction showed toxic activity against Artemia salina Leach larvae. The ethyl acetate fraction showed the highest toxic activity (LC50 of 316,22 ppm), and the n-hexan fraction (LC50 of 457,08 ppm).